The Boma: Can one chicken make a difference to a child's health? - International Livestock Research Institute (International Livestock Research Institute, 2022)
In 2014 a survey found that a quarter of children under 5 in Siaya County, western Kenya, were stunted. Stunting creates lifelong, chronic health issues and worse mental development. Better nutrition can help avoid stunting, but can be a struggle for families that are already lacking money, resources and access to support. What if there was a way to empower families by improving a simple resource they already have? Such as chickens, a small but ubiquitous livestock in rural communities. But proving this is not so easy. In our new episode of The Boma, we dive into the questions and answers to see if there really is a link between poultry and children's health.